Penggunaan Media PPT Interaktif Untuk Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Bahasa Jepang di SMA Negeri 1 Pangean - Wirma Lestari; Dini Budiani; Nana Rahayu (Journal on Education, 2024)
This study aims to examine whether the use of interactive PowerPoint can improve the motivation to learn Japanese at SMA Negeri 1 Pangean. The research employs an experimental method with a control class and an experimental class, using questionnaires as the data collection technique. The questionnaires were administered before and after the treatment. Data analysis in this study includes the validity and reliability of the questionnaires, normality test, t-test, and hypothesis testing using MS Excel 21. Based on the results of the questionnaires distributed to both the experimental and control classes, there were changes in motivation between the two classes. A significant change was observed in the experimental class that used interactive PowerPoint in their Japanese language learning.